Authentication Scheme for Phishing Prevention using 2FA with SHA-512 - Charu Singh, Smt. Meenu (International Journal of Advanced Science and Technology, 2020)
Phishing is a major problem of today’s world. In phishing, user education is not sufficient to prevent from phishing. Sometimes, educated person also fall into phishing. To prevent phishing, both the client side and server side plays significant role. In this proposed, we used 2FA with SHA 512 hashing function, to prevent from phishing. In 2FA two step verification is used for phishing prevention. Web Bluetooth API is connected with website and SHA 512 is used to check the integrity and in next factor acknowledgment is received whether is it phishing, legitimate or suspicious web link and then verification it is done by OTP, QR scan etc.